Pengaruh Servant Leadership Dan Keterikatan Kerja Terhadap Kinerja guru SMA Negeri di Kabupaten Ogan Komering Ilir - Liza Risdiyanti; Yasir Arafat; Andi Rahman (CV. Ulil Albab Corp, 2026)
Teacher performance is an important factor in improving the quality of education in high school. One of the efforts to improve teacher performance can be done through the implementation of the right leadership style and increasing the teacher's work attachment. This research aims to analyze the influence of servant leadership and work attachment on teacher performance at State High School in Ogan Komering Ilir Regency. The population in this study is all State High School teachers in Ogan Komering Ilir Regency, with a sample determined using certain techniques. Data collection is done through a questionnaire that has been tested for validity and reliability. Data was analyzed using inferential statistical analysis to determine the partial and simultaneous influence between variables. The research results show that servant leadership has a positive and significant effect on teacher performance, work attachment has a positive and significant effect on teacher performance, and servant leadership and work attachment simultaneously have a significant effect on teacher performance. This finding indicates that the implementation of leadership that serves and the improvement of teacher work engagement can be an effective strategy in improving teacher performance at the State High School of Ogan Komering Ilir Regency.